Analisis Penerapan Total Quality Management Guna Menjaga Mutu Produk pada Usaha Arang Halaban MJA di Kota Samarinda - Devita Maya Sari; Muhammad Zaini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Quality control in traditional manufacturing industries often faces quality inconsistency constraints as a result of the lack of standardization of work procedures and quality control. A strategy is needed to improve quality and productivity in order to continue to compete in the tight business competition. Through the implementation of Total Quality Management (TQM) carried out with the support of all aspects of the business not only focusing on one aspect has an important role in sustainable business and uses the Plan-Do-Check-Act (PDCA) cycle as a measuring tool that can realize policies to maintain, and improve or increase standards. This study aims to analyze the implementation of Total Quality Management (TQM) and quality conformity based on the Plan-Do-Check-Act (PDCA) cycle in the Halaban MJA Charcoal business (Mashurin Jaya Abadi). The research method used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and confirmatory descriptive questionnaires as supporting data. The results of the study indicate that the TQM elements of obsession with quality, scientific approach, and teamwork are still not optimal so they still need improvement. However, PDCA cycle-based evaluations show that they are not fully in accordance with the Plan–Do–Check–Act (PDCA) principles because they are not supported by written standard operating procedures (SOPs), process standards, and adequate evaluation documentation.